On the problems of monitoring the shadow economy - E. V. Baturina (Вестник университета)
The article presents the main provisions of the author’s Concept of monitoring the shadow economy through the economic and mathematical analysis of the shadow cashless cash flow. According to the author’s concept, the object of shadow economy monitoring has been specified, priority areas of shadow economy monitoring have been outlined, the tasks of ensuring economic security of the Russian Federation have been revealed. The necessity (relevance) of implementing the author's Concept has been substantiated: the disadvantages of existing methods of shadow economy assessment have been outlined and the advantages of the proposed author’s scientific approach allowing to minimise the above disadvantages have been presented. The result of a critical analysis of the shortcomings of the scientific idea itself has been presented and the further research directions have been determined.